Biomimetic regioselective and high-yielding Cu(i)-catalyzed dimerization of sinapate esters in green solvent Cyrene™: towards sustainable antioxidant and anti-UV ingredients. Issue 6 (11th March 2020) - Mention, Matthieu M.; Flourat, Amandine L.; Peyrot, Cédric; Allais, Florent
Abstract : β–β′ dimers of sinapate esters are anti-UV and antiradical chemicals. Abstract : Naturally occurring sinapic acid and its esters are anti-UV and antiradical chemicals. This work aimed at designing an industrially relevant sustainable synthetic pathway allowing their selective β–β′ dimerization to enhance their properties with a view to use them in commercial applications such as functional additives for cosmetics, plastics and food/feed. A copper(i )-catalyzed procedure involving pyridine and O2 from air was developed and greened up using the REACH-compliant bio-based solvent Cyrene™. Upon optimizing further through design of experiments, this sustainable synthetic process was successfully implemented to various sinapate esters and was validated on the multigram scale. Antiradical activities of the resulting β–β′ disinapate esters were benchmarked against commercial antioxidants, whereas their UV absorbance was compared to that of sinapoyl malate, a natural anti-UV compound found in plants and that of Octinoxate™, a widely used commercial sunscreen ingredient. Results showed that these dimers were better radical scavengers, and not only exhibited a better UV absorbance but also covered both UV-A and UV-B regions.